Comparative Study on the Effectiveness of Coumavec® and Zinc Phosphide in Controlling Zoonotic Cutaneous Leishmaniasis in a Hyperendemic Focus in Central Iran - A Veysi; H Vatandoost; MR Yaghoobi-Ershadi; MH Arandian; R Jafari; M Hosseini; H abdoli; Y Rassi; K Heidari; A Sadjadi; R Fadaei; J Ramazanpour; et al. (Tehran University of Medical Sciences, 2012)
Background: Zoonotic  cutaneous leishmaniasis (ZCL) is an increasing health problems in many rural areas of Iran. The aim of this study was to introduce a new alternative rodenticide to control the reservoirs of ZCL, its effect on the vector density and the incidence of the disease in hyperendemic focus of Esfahan County, central Iran. Methods: The study was carried out from January 2011 to January 2012. In intervention areas, rodent control operation was conducted using zinc phosphide or Coumavec®.Active case findings were done by house-to-house visits once every season during 2011-2012. To evaluate the effect of rodent control operation on the vector density, sand flies were collected twice a month using sticky traps. Results: The reduction rate of rodent holes inintervention areas with  Coumavec® and zinc phosphide were 48.46% and 58.15% respectively, whereas in control area results showed 6.66 folds intensification.The Incidence of ZCL significantly reduced in the treated areas. Totally, 3200 adult sand flies were collected and identified in the intervention and control areas. In the treated area with zinc phosphide, the density of Phlebotomus papatasi was higher in outdoors in contrast with the treated area by Coumavec® which the density of the sand fly was higher in indoors. Conclusion: Both rodenticides were effective on the incidence of ZCL and the population of the reservoirs as well. Coumavec® seems to be effective on the outdoor density of the vector. This combination of rodenticide-insecticide could be a suitable alternative for zinc phosphide while bait shyness or behavioral resistance is occurred.